Personal health coach – competence and social-professional role - Nowak, Paweł F (Polish Journal of Public Health, 2013)
In conditions of civilizational hurry and, at the same time, specialisation and professionalization of almost ever sphere of life, the need of consultancy services is emerging. The aim of this work is to present a new social phenomenon of the increasing popularity of personal health coaches, who provide consultancy in the field of preventive medicine and health promotion.The study shows the positive role of personal health coaches in social area and attempts to determine their competence in offered services e.g. organizing, planning and conducting individual health training. The fact of overly narrow understanding of the training of health and the concept of health coach, using only the resources in the area of physical culture, has been noted.